Analysis Of Indonesian Muslim Intention To Give Digital Intellectual Property Rights For Productive Waqf - Darfiti, Refit Gustaroska; Indra, Indra; Possumah, Bayu Taufiq (STIES INDONESIA PURWAKARTA Dan MES PURWAKARTA, 2024)
This study aims to analyze the factors that influence the intention of Muslims to donate their digital intellectual property rights as part of productive waqf assets using the Theory of Planned Behaviour (TPB) model. The research employs Structural Equation Modelling (SEM) and utilizes purposive sampling with primary data collected from a questionnaire distributed to selected respondents in 2022. The findings reveal that attitude toward behavior, subjective norm, and perceived behavioral control significantly and positively influence the intention to donate digital intellectual property for productive waqf. Among these, attitude toward behavior emerges as the most dominant factor. This indicates the potential for digital intellectual property to be a viable waqf asset, offering new opportunities for waqf institutions in Indonesia. The study is limited to Muslim individuals in the Jakarta area, focusing on copyright as a transferrable digital asset under Indonesian waqf and copyright laws. This research contributes to Islamic economics and waqf management by applying TPB in a digital context and providing practical insights for developing digital-based waqf programs.